Analysis of Institutional Frameworks and Mechanisms for Implementing Modern Social Approaches in Turkic States (International Journal of Scientific Trends, 2026)
This article examines the institutional frameworks and mechanisms for implementing modern social approaches in Turkic states within the context of globalization and socio-political transformation. The study analyzes the role of education systems, governance structures, and social institutions in shaping contemporary social policies. A comparative approach is applied to identify common patterns and national specificities in countries such as Uzbekistan, Türkiye, Kazakhstan, and Azerbaijan. The findings reveal that the integration of innovative technologies, competency-based education, and regional cooperation plays a crucial role in enhancing the effectiveness of social approaches.